SIGMA(2): A system for the integrative genomic multi-dimensional analysis of cancer genomes, epigenomes, and transcriptomes - Chari, Raj (BioMed Central, 2008)
BACKGROUND: High throughput microarray technologies have afforded the investigation of genomes, epigenomes, and transcriptomes at unprecedented resolution. However, software packages to handle, analyze, and visualize data from these multiple 'omics disciplines have not been adequately developed. RESULTS: Here, we present SIGMA(2), a system for the integrative genomic multi-dimensional analysis of cancer genomes, epigenomes, and transcriptomes. Multi-dimensional datasets can be simultaneously visualized and analyzed with respect to each dimension, allowing combinatorial integration of the different assays belonging to the different 'omics. CONCLUSION: The identification of genes altered at multiple levels such as copy number, loss of heterozygosity (LOH), DNA methylation and the detection of consequential changes in gene expression can be concertedly performed, establishing SIGMA(2 )as a novel tool to facilitate the high throughput systems biology analysis of cancer.